The Role of History as a Science in Sustainable Development - Arditya Prayogi (Westscience Press, 2023)
History is simply understood as events in the past. With this understanding, there is an assumption that history cannot contribute to the broad development process. This article aims to provide a conceptual description of the role of history as a science in the context of development in general and sustainable development in particular which is adapted to the objectives of sustainable development itself. This article is a historical conceptual article written with a qualitative descriptive approach supported by the use of data collection methods in the form of library research. From the results of the discussion, it is known that the concept of sustainable development can be traced from various works of social history so that a more detailed concept can be formulated today. History as a science also has an important relationship and role in the development process and sustainable development itself which can be seen from the existence of historical functions that can lead to historical consciousness.